Respuesta :
Hey there!
In order to solve this expression, we can use the distributive property. The distributive property states:
a(b+c) = ab+ac
Using this property along with addition and subtraction, we can simplify:
9-4(-a+9) + 3(7-2a) =
9 + 4a - 36 + 21 - 6a
Combine like terms:
(9-36+21) + (4a-6a) =
-6 - 2a
Hope this helps
In order to solve this expression, we can use the distributive property. The distributive property states:
a(b+c) = ab+ac
Using this property along with addition and subtraction, we can simplify:
9-4(-a+9) + 3(7-2a) =
9 + 4a - 36 + 21 - 6a
Combine like terms:
(9-36+21) + (4a-6a) =
-6 - 2a
Hope this helps